The Development Path Less Traveled : The Experience of Rwanda - Redifer, Laure (Departmental Papers; Departmental Paper ;, 2020)
This paper explores some of the key factors behind Rwanda key successes, including unique institution-building that emphasized governance and ownership; aid-fueled and government-led strategic investment in people, infrastructure, and high-yield economic activity; re-establishment and expansion of a domestic tax base; policies to reduce aid dependency by attracting private investment and bolstering exports; and a purposeful strategy to harness the economic power of gender inclusion.